2020
DOI: 10.1186/s40360-020-00436-z
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte-conditioned medium induces resistance of breast cancer cells to lapatinib

Abstract: Background: The existence of a cross-talk between peritumoral adipocytes and cancer cells has been increasingly investigated. Several studies have shown that these adipocytes protect tumor cells from the effect of anticancer agents. Methods: To investigate a potential protective effect of adipocyte-conditioned medium on HER2 positive breast cancer cells exposed to tyrosine kinase inhibitors (TKI) such as lapatinib, we analyzed the sensitivity of HER2 positive breast cancer models in vitro and in vivo on SCID m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 52 publications
2
17
0
Order By: Relevance
“…Similar to the findings reported by others [ 66 , 79 ], we did not observe any differences in the proliferation signalling pathways (i.e. PI3K, Akt, ERK1/2 and its phosphorylation, and NFĸB-p65) between the Dox and Dox+CM-treated MDA-MB-231 cells.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar to the findings reported by others [ 66 , 79 ], we did not observe any differences in the proliferation signalling pathways (i.e. PI3K, Akt, ERK1/2 and its phosphorylation, and NFĸB-p65) between the Dox and Dox+CM-treated MDA-MB-231 cells.…”
Section: Discussionsupporting
confidence: 91%
“…Leptin derived from obese adipocytes attenuated Tamoxifen’s® treatment efficacy [ 68 ], whereas MCP-1 protected breast cancer cells from 5-Fluorouracil [ 69 ]. Trastuzumab® antibody-mediated dependent cellular cytotoxicity was inhibited by adipocyte-derived factors in breast cancer cells [ 70 ], which was corroborated by 66 , for Lapatinib (tyrosine kinase inhibitor). Therefore, we propose that the treatment resistance observed in the Dox+CM group (increased cell-viability) may in part be as a result of secretory factors in the adipocyte-conditioned media stimulating the utilization/internalization of leptin and MCP-1 proteins by doxorubicin-treated MDA-MB-231 TNBC cells.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In primary breast cancer, adipocytes and adipocyte-derived factors have been linked to drug resistance and malignancy. In vitro, experiments with HER2+ BT474 and SKBR3 breast cancer cells cultured in the presence or absence of conditioned media from mature adipocytes demonstrated that in basal conditions, tyrosine kinase inhibitors (TKI) (often used to treat HER2+ breast cancer) induced p27 leading to apoptosis, which did not occur in the presence of adipocyte conditioned medium [40]. Contact of breast cancer cells with adipose tissue in vivo also led to reduced sensitivity to TKI [40].…”
Section: Adipose Tissue and Cancermentioning
confidence: 99%
“…In vitro, experiments with HER2+ BT474 and SKBR3 breast cancer cells cultured in the presence or absence of conditioned media from mature adipocytes demonstrated that in basal conditions, tyrosine kinase inhibitors (TKI) (often used to treat HER2+ breast cancer) induced p27 leading to apoptosis, which did not occur in the presence of adipocyte conditioned medium [40]. Contact of breast cancer cells with adipose tissue in vivo also led to reduced sensitivity to TKI [40]. In acute lymphoblastic leukemia (ALL), ALL cells migrate toward mature adipocytes in vitro, as well as subcutaneous and visceral adipose explants, which provide protection from daunorubicin and vincristine [41].…”
Section: Adipose Tissue and Cancermentioning
confidence: 99%